Expert Clinical Management of Inflammatory Immune-Related Arthritis in Patients with Cancer Receiving Immune Checkpoint Inhibitors - Sebastian Bruera; Mar Riveiro-Barciela; Alexa Meara; Maria E. Suarez-Almazor (Journal of Immunotherapy and Precision Oncology, 2025)
Introduction Treatment guidelines for immune-related inflammatory arthritis (irAE-IA) in patients with cancer receiving immune checkpoint inhibitors (ICIs) are vague with respect to the use of specific agents. Patients are usually referred to rheumatologists for treatment. We conducted a survey of expert rheumatologists to determine current practices. We also assessed experts’ views on the potential deleterious effects of various agents on tumor progression. Methods We conducted a survey of international experts in the treatment of irAE-IA, identified as members of collaborative scientific workgroups in this area. Experts were presented with a case of a patient with moderate irAE-IA and were asked about their preferred management including glucocorticoids, timing and initial choice of disease-modifying antirheumatic drugs (DMARDs), and perception of the deleterious effects of different agents on tumor progression. Results We approached 25 experts, of whom 19 (76%) responded. Most experts (63%) agreed on 20 mg or less of prednisone as initial dose. Experts selected methotrexate (41%) or tumor necrosis factor inhibitor (TNFi) (23%) as the initial DMARD if there was no improvement with corticosteroids; most experts (42%) would initiate DMARDs after 4 weeks. For patients whose initial DMARD therapy failed, the second choice was either a tumor necrosis factor inhibitor (TNFi) (38%) or interleukin-6 receptor antagonist (IL6ri) (33%). Experts were most concerned about the potential deleterious effects on tumor progression of abatacept and prednisone at doses of 20 mg or higher. Conclusion There was substantial heterogeneity in the initial management of irAE-IA. Further understanding of the pathophysiology of this immunotoxicity can assist in the classification of different presentations, selection of relevant outcomes, and planning of clinical trials to establish optimal therapeutic efficacy while minimizing potential deleterious effects of treatment on immune tumor responses.